A New Southern North Atlantic Isochron Map: Insights Into the Drift of the Iberian Plate Since the Late Cretaceous. Issue 12 (29th December 2017) - Macchiavelli, Chiara; Vergés, Jaume; Schettino, Antonio; Fernàndez, Manel; Turco, Eugenio; Casciello, Emilio; Torne, Montserrat; Pierantoni, Pietro Paolo; Tunini, Lavinia
Abstract: This paper presents a new southern North Atlantic plate model from Late Cretaceous to present, with the aim of constraining the kinematics of the Iberian plate during the last 83.5 Myr. This model is presented along with a detailed isochron map generated through the analysis of 3 aeromagnetic tracks and ~400 ship tracks from the National Centers for Environmental Information database. We present a new technique to obtain well‐constrained estimates of the Iberia‐North America plate motions from magnetic anomalies, overcoming the scarcity of large‐offset fracture zones and transform faults. We build an integrated kinematic model for NW Africa, Morocco, Iberia, Europe, and North America, which shows that the deformation is partitioned between Pyrenees and Betic‐Rif orogenic domain during the Late Cretaceous‐Oligocene time interval. In the Eastern Betics domain, the calculated amount of NW Africa‐Iberia convergence is ~80 km between 83.5 and 34 Ma, followed by ~150 km since the Oligocene. The motion of Iberia relative to Europe in the Central Pyrenees is characterized by overall NE directed transpressional motion during the Campanian and the Paleocene, followed by NW directed transpressional movement until the Lutetian and overall NNW directed convergence from Bartonian to Chattian. This motion occurs along the axis of the Bay of Biscay from the Santonian–Campanian boundary to the middle Priabonian, subsequently jumping to King's Trough at Anomaly 17 (36.62 Ma). Key Points: New southern North Atlantic (Iberia‐North America) isochron map from Late Cretaceous to present Iberia was an independent plate from 83.5 to ~20.1 Ma, and the convergence between NW Africa and Iberia was active since 83.5 Ma Iberia‐Europe convergence (Central Pyrenees) was NE directed from 83.5 to ~56 Ma, NW directed until ~46 Ma, and NNW directed till ~20.1 Ma